Blocks, Liquidity, and Corporate Control - Bolton, Patrick; Von Thadden, Ernst-Ludwig (Journal of Finance, 1998)
The paper develops a simple model of corporate ownership structure in which costs and benefits of ownership concentration are analyzed. The model compares the liquidity benefits obtained through dispersed corporate ownership with the benefits from efficient management control achieved by some degree of ownership concentration. The paper reexamines the free-rider problem in corporate control in the presence of liquidity trading, derives predictions for the trade and pricing of blocks, and provides criteria for the optimal choice of ownership structure.